LINKING MOUNTAIN IMAGE WITH PLACE-ATTACHMENT - Silva, Carla; Kastenholz, Elisabeth; Abrantes, José Luís (Journal of Tourism, Sustainability and Well-being, 2018)
Mountain tourism represents 15–20% of the tourist industry, corresponding to receipts of around 70–90 billion US$ per year. Mountains are attractive tourism destinations because people view them as natural and sacred places with plenty of social, cultural and symbolic meanings. The present study is a conceptual work that debates the link between mountain destination image with place-attachment by summarizing, systematizing and discussing the distinct, yet connected, image and place-attachment constructs. Based on an extensive literature review focusing on the concepts of place-attachment, destination image and social and cultural meanings of mountains, the study provides a framework which allows the assessment of the emotional and functional bonds that tourists can establish with mountain places. Systematization of the literature review should permit a deeper understanding of the diverse meanings and values associated with mountains, increasing our awareness of their social and cultural value. The model sheds light on the diverse dimensions of mountain destination image and their potential link to tourists’ place-attachment, which is most interesting for sustainable mountain tourism development. Although the model’s validation would further improve our understanding of the relationships between the constructs, the relations already identified in the literature review justify a consideration of the presented dimensions. This more detailed comprehension may enhance tourist mountain destination planning, as well as marketing and management, thus helping mountain DMOs promote distinct and unique mountain features that attract tourists and involve them emotionally with the mountain areas visited and dreamt of.